2004
DOI: 10.1177/107602960401000403
|View full text |Cite
|
Sign up to set email alerts
|

Sapheno-Femoral Junction Pathology: Molecular Mechanism of Saphenous Vein Incompetence

Abstract: A molecular mechanism responsible for varicose vein occurrence was investigated. The role of potential cell cycle regulator p21 and programmed cell death in the pathology leading to the proximal long saphenous vein (LSV) incompetence was investigated. Proximal LSV specimens were obtained from 40 patients with primary varicose veins who had undergone crossectomy. The expression of the p21, p53, and fas encoding genes was investigated by the means of real-time RT-QPCR. Immunostaining for gene product presence, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Urbanek et al (28) also found increased p53 expression in the distal GSV of young patients. There is evidence that surgical trauma and modified hemodynamics are associated with endothelial and smooth muscle cell damage.…”
Section: Discussionmentioning
confidence: 86%
“…Urbanek et al (28) also found increased p53 expression in the distal GSV of young patients. There is evidence that surgical trauma and modified hemodynamics are associated with endothelial and smooth muscle cell damage.…”
Section: Discussionmentioning
confidence: 86%
“…Initially, the medial layers of smooth muscle decrease in thickness, which is attributed to apoptosis of the smooth muscle cells. This is followed by down-regulation of pro-apoptotic factors and up-regulation of anti-apoptotic proteins (417-420) with smooth muscle cell hypertrophy (418,419). Alterations in gene expression were consistent with changes in smooth muscle actin functionality and contractility (421).…”
Section: Etiology Of Varicose Veinsmentioning
confidence: 95%
“…[4][5][6] Studies have found that hypoxia can induce down-regulate apoptosis, acting as a cell cycle inhibitor, which results in hypertrophy of smooth muscle cells of the vein walls, thus affecting the remodeling of vein walls. 7,8 A decrease in expression of the Bax gene protein has been shown to reduce apoptosis of venous smooth muscle cells, and the apoptosis of varicose vein walls was found to be significantly lower than that of normal vein walls. 9 Thus, apoptosis of vein walls results from a metabolic imbalance in endothelial cells and smooth muscle cells, suppression of the endogenous apoptosis channel, cell accumulation, aging and structural abnormalities, all of which lead to changes in venous wall components and structure.…”
Section: Introductionmentioning
confidence: 99%